ON THE SOME EXTREMAL PROBLEM - Tonoyan, L. G. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2002)
In the paper the existence of an optimal pair of an initial boundary problem for some class of the nonlinear evolutionary equations of the fourth order with variable coefficients is proved.